PERILAKU KONSUMEN ROKOK : KASUS DI SUPERMARKET "ABC" SURABAYA - Imam Hldayat, Syarif (MAPETA, 2008)
Smoke is still live choice and habit to most people in the world among activities. Eventhough the govenunent forbid to smoke, really still do it as habit. In the other hand cigarette tax has a big contributed to national income so the issues always the big topics discussion between pro and contra from time to time. The purpose of study is to know variables of knowledge, motivation, life style, information, experince, image, habit, income, and family affected to consumer behavior cigarette "X". Based on factor analysis shows thai: individual factors (knowledge, motivation, life style), phsycological process (information, experience, image), environmental factors (habit, income, family) influenced to consumer behavior cigarette A and B. As recommendation the seller should concern and focus strategy to maintain and increase sales especially in three factors mentioned above. Key words: consumer behavior, cigarette